Avaliação da adequabilidade da amostra sobre a detecção das lesões precursoras do câncer do colo do útero em uma unidade básica de saúde - Abreu, Keite Carla Abade Cerqueira de (2020)
The Cervical cancer represent fourth place in the incidence and mortality of the female population. The Health Organization keeping efforts to combat this disease and have focused on the tracking program, a secondary prevention policy aimed at an asymptomatic target population to identify women most likely to have the disease itself or a precursor to the disease. Tracking is carried out by means of an examination, the oncotic cytology, better known as Papanicolaou. Given its epidemiological, social and economic magnitude, this type of cancer represents an important public health problem. Studies show results where the exam collection technique is associated with poor quality, contributing to a high rate of false-negative results. In this sense, the objective of the research was to verify if the adequacy of the sample influences the detection of precursor lesions of cervical cancer. This is a documentary research, a cross-sectional study with a quantitative approach, developed in the city of São Paulo, in a Basic Health Unit (UBS), where I work as a Family Health Strategy Nurse. Papers of Papanicolaou exams performed in the years 2017 to 2018 at UBS were included from the Register Book and the analysis of Excel spreadsheets in which the monthly condensates of Papanicolaou exam collections are registered. A total of 3847 Papanicolaou collections were analyzed. Through descriptive statistical analysis, it was demonstrated that the detection of precursor lesions of cervical cancer varies with suitability of the sample. In the altered results that were presented, the adequacy of the collections analyzed from the representation of the cells that demonstrate quality was present in 77.2% of the collected samples. We conclude that there is a need to carry out actions aimed at continuing education and updating health professionals who perform Pap smear collection, in order to improve quality by reducing the frequency of false-negative results, bringing more accurate and safe diagnoses.